Degradasi Zat Warna Artifisial Limbah Tekstil Dengan Advanced Oxidation Processes Menggunakan Katalis Nanopartikel Ce/Karbon - Farhiz Lagan; Edy Saputra; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
One of the innovation textile waste processing is advance oxidation processes using peroxymonosulfate and catalyst nanoparticle Ce/carbon. This study was aimed to decrease content of artificial dye waste and determined the optimum conditions by using catalyst nanoparticle Ce/carbon. Catalyst synthesis was processed in hydrothermal autoclave at temperature 1800C for 18 hours, it convert D-glucose into black carbon, then impregnated with catalyst metal Ce by 3% and 5% by weight, after that catalyst calcined by N2 at temperature 5000C for 4 hours. Adsorption of artificial dye textile waste was held 25 ppm for 2 hours with concentration of catalyst 0,4 gr/L. The optimum adsorption of artificial dye textile waste with catalyst concentration 0,4 gr/L was is 12,921 with adsorption percentage reached 48,32%.Keyword: advanced oxidation processes, nanopartikel Ce/carbon, dye